2022
DOI: 10.1177/00031348221121547
|View full text |Cite
|
Sign up to set email alerts
|

Automated Electronic Frailty Index is Associated with Non-home Discharge in Patients Undergoing Open Revascularization for Peripheral Vascular Disease

Abstract: Background Frailty is associated with adverse surgical outcomes including post-operative complications, needs for post-acute care, and mortality. While multiple frailty screening tools exist, most are time and resource intensive. Here we examine the association of an automated electronic frailty index (eFI), derived from routine data in the Electronic Health Record (EHR), with outcomes in vascular surgery patients undergoing open, lower extremity revascularization. Methods A retrospective analysis at a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The availability of tools such as the eFI is increasingly important in the perioperative realm, as higher frailty scores are indicative of increased postoperative care needs, including hospital length of stay and discharge to transitional care facilities, 30-day readmission rates, and all-cause mortality. 1,3,8 However, these tools demonstrate substantial heterogeneity in their association with postoperative surgical complication risk; therefore, a closer examination is necessary. 8 In a previous study, Callahan et al 1 grouped patients into 3 frailty categories using eFI scores (fit, prefrail, and frail) and found that a patient's likelihood for worse outcomes increased as the severity of frailty increased.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The availability of tools such as the eFI is increasingly important in the perioperative realm, as higher frailty scores are indicative of increased postoperative care needs, including hospital length of stay and discharge to transitional care facilities, 30-day readmission rates, and all-cause mortality. 1,3,8 However, these tools demonstrate substantial heterogeneity in their association with postoperative surgical complication risk; therefore, a closer examination is necessary. 8 In a previous study, Callahan et al 1 grouped patients into 3 frailty categories using eFI scores (fit, prefrail, and frail) and found that a patient's likelihood for worse outcomes increased as the severity of frailty increased.…”
Section: Introductionmentioning
confidence: 99%
“…8 In a previous study, Callahan et al 1 grouped patients into 3 frailty categories using eFI scores (fit, prefrail, and frail) and found that a patient's likelihood for worse outcomes increased as the severity of frailty increased. 2,3 The eFI calculation includes comorbidities, which could also play a role in adverse outcomes (eTables 1 and 2 in Supplement 1). Furthermore, while the eFI has been constructed and validated in an accountable care organization in adults older than 65 years, its with critical illness not expected to survive without the operation) or VI (indicating individuals with brain death being considered as organ donors) and patients with insufficient historical data to calculate the eFI (eTable 6 in Supplement 1).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations